Institutional Strategies for Regulating Artificial Intelligence in Higher Education: A Comparative Analysis of Ukrainian Experience - Sarajeva, Olga; Kokhan, Larysa (Skhid, 2026)
This article examines the process of integrating generative artificial intelligence (GenAI) into Ukraine’s educational ecosystem during 2025–2026. Drawing on a comparative analysis of regulatory frameworks and academic integrity codes at leading universities – including Taras Shevchenko National University of Kyiv, Igor Sikorsky Kyiv Polytechnic Institute, Borys Grinchenko Kyiv Metropolitan University, and O. M. Beketov National University of Urban Economy in Kharkiv, the study identifies four key institutional strategies for AI regulation: from strict control and ethical barriers to practical utility and full academic freedom. The analysis reveals a sociological phenomenon of “dual reality,” characterised by a gap between the latent mass use of technology by over 80% of students and the official discourse of higher education institutions, where only 26% of respondents are willing to openly declare their use of AI. At the same time, the study presents the GAIDeT methodological model (Generative AI, Author, Input, Declaration, Ethics, Transparency) as a validated instrument for ensuring academic integrity and legitimising the use of AI in the research process. The study establishes that shifting from a paradigm of “strict oversight” to a model of transparent partnership ensures the sustainable development of Ukrainian higher education in the context of global digital competition and the renewal of the educational environment. The research concludes that this approach becomes a catalyst for transforming the role of the teacher – from a transmitter of knowledge to a moderator of intellectual inquiry, while preserving the uniqueness and inviolability of human creative agency.